On identification errors in Scytalopus speluncae (Ménétriés) and S. pachecoi Maurício from southern Brazil with new data on distribution and biogeography of these taxa (Aves: Rhinocryptidae) - Maurício, Giovanni Nachtigall; Bornschein, Marcos Ricardo (Zootaxa, 2017)
The Brazilian tapaculo Scytalopus speluncae species-group has been the subject of intense taxonomic work in the past 18 years, with six new species being named in that time lapse and other taxonomic problems having been highlighted (Bornschein et al. 1998, 2007; Maurício 2005; Raposo et al. 2006, 2012; Mata et al. 2009; Whitney et al. 2010; Maurício et al. 2010, 2014; Pulido-Santacruz et al. 2016). One of the most persistent of these problems involves the oldest name in this group, S. speluncae (Ménétriès), and the taxa it may represent. Historically, this name has been applied to the dark gray populations (whose adult males have plain gray flanks) occurring along coastal mountains between Espírito Santo and São Paulo states in Brazil (Raposo et al. 2006; Maurício et al. 2010). Subsequently, dark gray populations from the Brazilian states of Paraná, Santa Catarina, and Rio Grande do Sul, as well as paler gray birds with black-barred brown flanks from northeastern Argentina (Misiones Province) and adjacent southern Brazilian states were also subsumed under S. speluncae (Bornschein et al. 1998; Maurício 2005; Maurício et al. 2010). However, the paler gray, barred populations from Argentina and some parts of Santa Catarina and Rio Grande do Sul have proved to be a distinct and partially sympatric species named S. pachecoi Maurício, which was shown to be not closely related to S. speluncae, but rather pertains to the very divergent clade of S. novacapitalis Sick and related forms (Maurício 2005; Mata et al. 2009). On the other hand, the dark-gray populations coming from Espírito Santo south to Rio Grande do Sul continued to be identified as S. speluncae.